2013
DOI: 10.1007/s12664-013-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

CT enterography: state-of-the-art CT technique for small bowel imaging

Abstract: Multi-detector computed tomography has become a first-line imaging modality for the evaluation of small bowel disease. Its high speed and resolution ensure excellent imaging of the small bowel with simultaneous evaluation of the lumen and wall, adjoining mesentery, and extraluminal structures in the abdominal cavity. Optimal luminal distension is an important prerequisite. Computed tomography enterography (CTE) is a dedicated adaptation for the study of the small bowel. This review discusses CTE with emphasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…It can also help in localisation of active bleeding as the presence of active GI bleeding would be seen as a focal area of hyperdense attenuation in the bowel lumen on plain scan or as focal area of contrast enhancement or extravasation into the lumen on a contrast-enhanced study [84]. Lee and co-workers evaluated the diagnostic performance of CTE in 65 patients of OGIB [85].…”
Section: Management Of Small Bowel Bleedmentioning
confidence: 99%
“…It can also help in localisation of active bleeding as the presence of active GI bleeding would be seen as a focal area of hyperdense attenuation in the bowel lumen on plain scan or as focal area of contrast enhancement or extravasation into the lumen on a contrast-enhanced study [84]. Lee and co-workers evaluated the diagnostic performance of CTE in 65 patients of OGIB [85].…”
Section: Management Of Small Bowel Bleedmentioning
confidence: 99%
“…Radiation concern is an important issue in CTE because patients with Crohn disease are relatively younger and are expected to undergo multiple follow-up CT studies 35. Desmond et al36 reported that portion of CT scans contributing to cumulative effective dose increased from 46.3% during the first 5 years to 84.7% during the final 5 years in their 15-year study of patients with IBD.…”
Section: Cte Findings Of Intestinal Bdmentioning
confidence: 99%
“…CT enteroclysis promotes a more efficient intestinal distension, especially of the duodenum and jejunum. However, it is less accepted by patients owing to the need to pass an enteric tube for preparation (32) . Wold et al (33) found no difference in the quality of intestinal distension promoted by CT enteroclysis and CT enterography.…”
Section: Resultsmentioning
confidence: 99%